1987
DOI: 10.1128/iai.55.5.1101-1105.1987
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of complement component C3 synthesis in macrophagelike cell lines by group B streptococci

Abstract: Complement levels and complement activation are key determinants in streptococcus-induced inflammatory responses. Activation of macrophage functions, such as complement synthesis, by group B streptococci (GBS) was examined as a possible component of GBS-induced chronic inflammation. Using an enzyme-linked immunosorbent assay, secreted C3 from mouse macrophagelike cell lines (PU5-1.8 and J774A.1) was monitored after cultivation with GBS. Whole, heat-killed GBS (1 to 10 CFU per macrophage) of both type Ia and II… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

1993
1993
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 31 publications
1
6
0
Order By: Relevance
“…On the other hand, addition of latex beads in the same way resulted in a C3 concentration of 5.6 ng/ml. This lack of a stimulatory effect is in agreement with previous reports (16,29).…”
Section: Methodssupporting
confidence: 94%
See 1 more Smart Citation
“…On the other hand, addition of latex beads in the same way resulted in a C3 concentration of 5.6 ng/ml. This lack of a stimulatory effect is in agreement with previous reports (16,29).…”
Section: Methodssupporting
confidence: 94%
“…Stimulation of C3 biosynthesis has been reported in mouse macrophage-like cell lines after treatment with whole, heatkilled streptococci, while latex beads were ineffective (16).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study we analyzed the entry and subsequent survival of nonopsonized and opsonized GBS in macrophages. For this we used the well-established macrophage-like mouse cell line J774, which has features similar to those of normal macrophages and has frequently been used in functional studies on the phagocytosis of GBS (16,17,28).…”
Section: Discussionmentioning
confidence: 99%
“…Phagocytosis of the nonencapsulated isolates might explain why they did not induce C3 secretion; however, C3 was secreted in response to phagocytized Candida albicans (data not shown). Goodrum (16) reported that stimulation of C3 from macrophages by group B streptococci could be inhibited by cytochalasin B but that this treatment did not inhibit induction of C3 by endotoxin. The phagocytic process per se was not sufficient to induce C3 from macrophages, since ingestion of latex beads did not induce C3.…”
Section: Discussionmentioning
confidence: 99%
“…ELISA for C3. An ELISA for murine C3 was developed as described by Goodrum (16). Wells of 96-well, flat-bottom microtiter plates (Immulon IV) were coated with 0.1 ml of a 1:750 dilution of goat anti-mouse C3 (Cooper Biomedical) diluted in coating buffer (0.1 M NaHCO 3 ; pH 8.2).…”
Section: Methodsmentioning
confidence: 99%